Pinning Synchronization of Delayed Neural Networks with Nonlinear Inner-Coupling - Yangling Wang; Jinde Cao (Discrete Dynamics in Nature and Society)
Without assuming the symmetry and irreducibility of the outer-coupling weight configuration matrices, we investigate the pinning synchronization of delayed neural networks with nonlinear inner-coupling. Some delay-dependent controlled stability criteria in terms of linear matrix inequality (LMI) are obtained. An example is presented to show the application of the criteria obtained in this paper.